C.V.D. annual report: January, 1967 research project ru27-1 : analogue study of semiconductor device structures - Andrew, R.; Loeb, H. W. (College of Aeronautics, 1967)
The e::tension of the resistance network analogue method to the study of a M.O.S.T. structure is described. By means of an iterative technique, data regarding channel current, field distribution, surface charge and position of pinch-off point as function of gate and drain voltagen can be obtained which do not involve the usual 'gradual' channel approximation Results for a particular device geometry are presented. A discussion of a digital computer approach to the solution of semiconductor device current flow problems is included, together with preliminary results.